Edaphic Growth Conditions Centaurium erythraea Rafh. in Conditions of Transcarpathia - Grygoryuk, Ivan; Feketa, Iryna (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The results of researches of the еdaphic growth conditions Centaurium erythraea Rafh. in conditions of the Transcarpathia are represented in this article. Centaurium erythraea often grows in the Carpathians at meadows, forest glades, mountain slopes. The plant is found in small groups in the phytocenosis. We conducted soil conditions studies at 5 locations in different natural zones of Transcarpathia. During The plant‘s distribution, the ecological and soil conditions of the growth of Centaurium erythraea were determined. The soil analysis was carried out at the points where plant groups with a predominance of Centaurium erythraea of an average in natural populations over an area of 5 m2. Plants of Centaurium erythraea are unpretentious to the soil and climatic conditions, grow in different soils. Particularly widespread acquires Centaurium erythraea on sod-podzolic soils, as the main component of the mixtures with grasses. But this thesis is not confirmed yet in terms of the Carpathian region. Given this current is to clarify areas of distribution of a Centaurium erythraea in the wild state and its culture in crops, in order to establish demands to the soil conditions and the definition of the yield level, various mechanical composition and physical and chemical properties of soils.